Strategi Pemasaran Usaha Kopi Bubuk Merek Liber.co (Studi Kasus UMKM Liber.co di Kecamatan Sambas Kabupaten Sambas) - Savitri, Chery Andralea (Master of Management Diponegoro University, 2023)
The liber.co ground coffee business is a business that processes local Sambas Liberika coffee beans into coffee powder products in standing pouch packaging. This effort can be the best priority in improving the economic welfare of coffee farmers and introducing local liberal coffee products throughout Indonesia and abroad. However, the marketing activities of the liber.co ground coffee business have not been maximally distributed, so it requires an effective distribution channel. This study aims to analyze and determine alternative marketing strategies for the liber.co coffee powder business in Sambas Regency. This research was analyzed in 3 (three) stages, namely, 1) the input stage which analyzed IFE and EFE, 2) the internal and external factor matching stage with SWOT, and the strategic decision stage using QSPM. Determining strategies using the QSPM method produces alternative strategies, namely developing and increasing product existence on websites and digital social media in marketing up-to-date products, maintaining product quality and durability to increase consumer satisfaction, and strengthening cooperation with distributors to coffee suppliers, expanding distribution or partners other work. These three strategies are alternative strategies chosen to support the marketing strategy of the liber.co brand ground coffee business in marketing activities. Keywords: Liber.co Ground Coffee, Marketing Strategy, IFE EFE Analysis, SWOT, QSPM